O masculino e o feminino na literatura de cordel publicada em São Paulo - Barros, Miguel Pereira (2014)
This research belongs to the Center of Studies of Gender, Race and Age (NEGRI), of the Master Degree of Social Psychology in the Catholic University of São Paulo. Our works are developed with the objective to comprehend gender inequality, race and age understanding the ways in which ideology is use, through symbolic forms, to maintain asymmetric relations. We understand gender as cultural, historical and social buildings. The study object of this dissertation is cordel booklets produced and reproduced in São Paulo. We directed our analysis to the ideology in the speeches about masculine and feminine in this literature. It is worth saying that this is the first research which works with popular culture at NEGRI, aiming to perceive how a midia, such as cordel booklets, influences at the culture of a big city such as São Paulo. Our theoretical references are ideology theory of John B. Thompson (2009) and the gender studies of Joan Scott (1995). In the methodological field, the method adopted was the hermeneutics of depth defined by John B. Thompson (2009) because allow us to define the social historical context of production and reproduction of the media analyzed, and the operation modes of ideology. The analysis appointed to the male majority at the production of cordel booklets. We also appointed the constructions of harsh sceneries, characterized, mainly, for the violence, both to attack as to defend. We also, apprehend that the male characters presented particulars related to force, brutality, courage and independence while the female characters were beauty, weak, submitted and dependent of men. Only in four cordel booklets we encounter women transgressors of this gender model. In that way we confirmed the gender asymmetric remains at the production of cordel booklets and the speeches published in the stories